Kiš in Andrić - možna poetološka vzporednica - Vladušić, Slobodan (Slavistična revija, 2017)
The author's point of departure is the observation that both Andrić and Kiš use historical documents in the process of their writing, although they achieve that in different ways. This difference is examined in the context of a monumental challenge to which both authors had to respond, i.e., the dominance of information over the story. The poetological reaction to this challenge is different for each author, but a certain position is common to both of them: they both differentiate between the officially accepted history, which they equate with fiction, and non-accepted knowledge about the past. They believe that literature has the power to gather elements of this non-accepted knowledge about the past and confront the official history with them.
Keywords: Andrić, Ivo, 1892-1975; avtopoetika; history; Kiš, Danilo, 1935-1989; poetika; primerjalne študije; srbska književnost; srbski pisatelji; zgodba; zgodovina